METHODS OF EXPERT ASSESSMENT OF STUDENTS' RELATIONSHIPS IN DISTANCE EDUCATION IN THE METHOD OF STRELYAU Y.A. - Bekmuxammedov Bunyodbek Nurmuxammad o‘g‘li; Jarilkaganova Aysuliw Yerkinbay qizi (Bright Mind Publishing, 2025)
This article presents expert assessment methods based on the concepts of Strelyau Ya. and Kuznetsova A.M. in the assessment of student behavior in distance education. On the basis of criteria, it is possible to assess the level of student learning, stability, continuity in activities and psychological reactions. Each methodology is based on the sum of points, and these results are presented graphically. Through the statistical results of the assessment, it will be possible to determine whether the student is the same or changed. The article describes the evaluation mechanism with analysis, tables and graphs, by the example of a real learning process.
Keywords: Distance learning, student behavior, expert assessment, strelyau concept, kuznetsova methodology, evaluation criteria, level of uniformity, graphic analysis.